Philosophical Legal Grounds of the Regulation of Animal Welfare in International and National Law - Zubchenko, Nadiia I.; Зубченко, Надежда Игоревна; Зубченко, Надія Ігорівна (My University, 2014)
The aricle describes philosophical, ethical and teoreical grounds of legal regulaion of animal welfare. A part of atenion paid to the internaional and national reglamentaion of animal welfare. A research also deals with the analysis of the legal regulaion in the area of the treatment of animals in Ukraine and perspecives of its development. Analysis of the Law of Ukraine On the Protecion of Cruelty to Animals allows to conclude about an integrated aprproach to the protecion of animals from abuse, the systemaic nature of the rules and mechanisms for their implementaion. Actually adopion of the Law of Ukraine formed a new legal insitute associated to the treatment of pets. Previously, these maters were governed by separate norms of administrarive and partly of the criminal law relaing to criminal liability for cruelty to animals.
Zubchenko N. Philosophical Legal Grounds of the Regulation of Animal Welfare in International and National Law / N. Zubchenko // Evropsky Politicky a Pravni Diskurz / European Political and Law Discourse. – 2014. – № 2. – P. 19–25.
Keywords: animal welfare; international standards; international law; protection of animals; благополучие животных; международное право; защита животных; добробут тварин; міжнародні стандарти; міжнародне право; захист тварин; международные стандарты